2017
DOI: 10.1017/jns.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

A hot water extract of turmeric (Curcuma longa) suppresses acute ethanol-induced liver injury in mice by inhibiting hepatic oxidative stress and inflammatory cytokine production

Abstract: Turmeric (Curcuma longa) is a widely used spice that has various biological effects, and aqueous extracts of turmeric exhibit potent antioxidant activity and anti-inflammatory activity. Bisacurone, a component of turmeric extract, is known to have similar effects. Oxidative stress and inflammatory cytokines play an important role in ethanol-induced liver injury. This study was performed to evaluate the influence of a hot water extract of C. longa (WEC) or bisacurone on acute ethanol-induced liver injury. C57BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 52 publications
4
45
0
Order By: Relevance
“…Palmitate significantly enhanced intracellular RDS production in HepG2 cells, whereas this was almost completely prevented by TENE ( Figure 4). On line with this result, a hot water extract of turmeric inhibits ethanol-induced liver injury by inhibiting hepatic oxidative stress and production of inflammatory cytokines tumor necrosis factor (TNF)-α and interleukin (OL)-6 (Uchio et al, 2017). On addition, turmeric extract and its active compound curcumin also exhibited hepatoprotective activity against carbon tetrachloride-induced injury in mice by suppressing hepatic oxidative stress (Lee et al, 2016).…”
Section: Effects Of Tene On Palmitate-induced Lipid Accumulation and mentioning
confidence: 80%
See 1 more Smart Citation
“…Palmitate significantly enhanced intracellular RDS production in HepG2 cells, whereas this was almost completely prevented by TENE ( Figure 4). On line with this result, a hot water extract of turmeric inhibits ethanol-induced liver injury by inhibiting hepatic oxidative stress and production of inflammatory cytokines tumor necrosis factor (TNF)-α and interleukin (OL)-6 (Uchio et al, 2017). On addition, turmeric extract and its active compound curcumin also exhibited hepatoprotective activity against carbon tetrachloride-induced injury in mice by suppressing hepatic oxidative stress (Lee et al, 2016).…”
Section: Effects Of Tene On Palmitate-induced Lipid Accumulation and mentioning
confidence: 80%
“…The beneficial effects of turmeric extract on hepatic disease have also been demonstrated in the chemical-induced liver injury in which administration of turmeric extract was associated with a significant reduction in the hepatic oxidative states (Uchio et al, 2017;Lee et al, 2016). A dietary supplement containing turmeric extract also prevented the development of nonalcoholic fatty liver disease (NAFLD) by modulating the levels of serum glucose and leptin in patients with NAFLD (Navekar et al, 2017).…”
Section: Effects Of Tene On Palmitate-induced Lipid Accumulation and mentioning
confidence: 97%
“…26 We recently reported that a hot water extract of C longa (WEC) suppresses acute ethanol-induced liver injury by inhibiting hepatic oxidative stress and inflammatory cytokine production. 27 Topical application of an extract of C longa was also shown to improve skin conditions 28 ; however, the influence of intake of WEC on human skin conditions has not yet been clarified.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…For example, aqueous extracts of C longa have been reported to exhibit antioxidant and anti‐inflammatory activities, to promote corneal wound healing, and to have antidepressant and an anticancer effects . We recently reported that a hot water extract of C longa (WEC) suppresses acute ethanol‐induced liver injury by inhibiting hepatic oxidative stress and inflammatory cytokine production . Topical application of an extract of C longa was also shown to improve skin conditions; however, the influence of intake of WEC on human skin conditions has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Several therapeutic and pharmacologic properties of C. longa have recently been reported; antioxidant activity [13][14][15], cardiovascular and anti-diabetic effects [16][17][18] inflammatory and edematic disorders [19][20][21], anti-cancer [22,23], [26,27], anti-microbial [24][25], hepatoprotection [26,27] protection against Alzheimers [28][29][30], photo protector [12,31]. Although majority of spices and medicinal herbs are commonly presumed to be safe, adverse effects occasionally arise after the consumption of herbal products.…”
Section: Introductionmentioning
confidence: 99%